CDKL5 knockout leads to altered inhibitory transmission in the cerebellum of adult mice. (3rd May 2016) - Sivilia, S.; Mangano, C.; Beggiato, S.; Giuliani, A.; Torricella, R.; Baldassarro, V. A.; Fernandez, M.; Lorenzini, L.; Giardino, L.; Borelli, A. C.; Ferraro, L.; Calzà, L.
Abstract : CDKL5 deletion impairs the establishment of a correct GABA‐ and glutamatergic cerebellar network, leading to locomotion abnormalities. Abstract : Mutations in the X‐linked cyclin‐dependent kinase‐like 5 gene ( CDKL5 ) are associated to severe neurodevelopmental alterations including motor symptoms. In order to elucidate the neurobiological substrate of motor symptoms in CDKL5 syndrome, we investigated the motor function, GABA and glutamate pathways in the cerebellum of CDKL5 knockout female mice. Behavioural data indicate that CDKL5 ‐KO mice displayed impaired motor coordination on the Rotarod test, and altered steps, as measured by the gait analysis using the CatWalk test. A higher reduction in spontaneousGABA efflux, than that in glutamate, was observed in CDKL5 ‐KO mouse cerebellar synaptosomes, leading to a significant increase of spontaneous glutamate/GABA efflux ratio in these animals. On the contrary, there were no differences between groups in K + ‐evoked GABA and glutamate efflux. The anatomical analysis of cerebellar excitatory and inhibitory pathways showed a selective defect of the GABA‐related marker GAD67 in the molecular layer in CDKL5 ‐KO mice, while the glutamatergic markerVGLUT1 was unchanged in the same area. Fine cerebellar structural abnormalities such as a reduction of the inhibitory basket 'net' estimated volume and an increase of the pinceau estimated volume were also observed in CDKL5 ‐KO mice. Finally, the BDNF mRNA expression level in the cerebellum, but not in the hippocampus, was reduced compared with WT animals. These data suggest that CDKL5 deletion during development more markedly impairs the establishment of a correct GABAergic cerebellar network than that of glutamatergic one, leading to the behavioural symptoms associated with CDKL5 mutation.